2014
DOI: 10.1021/nl4037438
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of Spectral and Angular Distribution of Scattering from Single Gold Nanoparticles by Subwavelength Interference Layers

Abstract: Localized surface plasmon resonance (LSPR) as the resonant oscillation of conduction electrons in metal nanostructures upon light irradiation is widely used for sensing as well as nanoscale manipulation. The spectral resonance band position can be controlled mainly by nanoparticle composition, size, and geometry and is slightly influenced by the local refractive index of the near-field environment. Here we introduce another approach for tuning, based on interference modulation of the light scattered by the nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…1d) exhibits green doughnut-shaped patterns, rather than the dots pattern as shown in AuNPs supported by other substrates. As revealed by Ref [24] and our previous study [25], these substrate-induced AuNPs' optical properties are the result of resonance coupling between LSPs and optical cavity modes.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…1d) exhibits green doughnut-shaped patterns, rather than the dots pattern as shown in AuNPs supported by other substrates. As revealed by Ref [24] and our previous study [25], these substrate-induced AuNPs' optical properties are the result of resonance coupling between LSPs and optical cavity modes.…”
mentioning
confidence: 56%
“…photoemission enhancement [15], surface enhanced Raman scattering [16][17][18], bio-or chemical sensing [12,[19][20][21][22] and temperature sensing [23]. Recently Wirth et al discovered that tuning the position of individual NPs with respect to the mirror can effectively alter the cavity-NP coupling states, leading to the spectral and directional reshaping of nanoparticle scattering [24]; while we found that this position tuning can also induce a large modification of single NP scattering intensity [25].…”
mentioning
confidence: 59%
“…Taking Figure 1A (II) as an example to explain the interaction process between light and nanostructure, it can be divided into three consecutive steps (Wirth et al, 2014): (1) when the light wave irradiates on the dielectric layers (PE/gold film), thereby forming a specific electromagnetic field in the space layer; (2) the generated electromagnetic field interacts with nanorods and induces the light scattering; and (3) the scattered light from nanorods interfere with the reflected light from the space layer. In the gold film, the transmission light can be ignored because the thickness of the gold film is 45 nm, which is larger than the penetration depth of the light beam in the gold layer (about 25-30 nm) (Groeblacher et al, 2007).…”
Section: Numerical Simulationmentioning
confidence: 99%
“…25 LSPR characters strongly depend on the shape, size and compositions of nanoparticles and the surrounding dielectric environment. 30,31 Compared to those used in uorescent sensing, plasmonic nanomaterials used in LSPR biosensing are more sensitive, non-toxic, and do not suffer from background suppression. The LSPR scattering spectroscopy of a single plasmonic nanoparticle (PNP) could be easily performed by dark-eld microscopy and a microspectral analyzer, and the notable spectral shis indicate the refractive index of the microenvironment surrounding an individual nanoparticle.…”
Section: Introductionmentioning
confidence: 99%